2015
DOI: 10.1096/fj.14-269811
|View full text |Cite
|
Sign up to set email alerts
|

1,25-Dihydroxyvitamin D regulates expression of the tryptophan hydroxylase 2 and leptin genes: implication for behavioral influences of vitamin D

Abstract: To investigate vitamin D-related control of brain-expressed genes, candidate vitamin D responsive elements (VDREs) at 27/210 kb in human tryptophan hydroxylase (TPH)2 were probed. Both VDREs bound the vitamin D receptor (VDR)-retinoid X receptor (RXR) complex and drove reporter gene transcription in response to 1,25-dihydroxyvitamin D 3 (1,25D). Brain TPH2 mRNA, encoding the rate-limiting enzyme in serotonin synthesis, was induced 2.2-fold by 10 nM 1,25D in human U87 glioblastoma cells and 47.8-fold in rat se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
93
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(100 citation statements)
references
References 45 publications
6
93
0
1
Order By: Relevance
“…Interestingly, the IBS-C patients in this population were the most responsive to vitamin D supplementation in terms of a striking improvement across nearly all IBS symptoms. 47 Because IBS-C patients are thought to possess lower gut serotonin levels, 48 the responsiveness of these patients to vitamin D supplementation is consistent with the actions of vitamin D to raise gut TPH1/serotonin levels 25 and with our current hypothesis that vitamin D, via induction of the intestinal TPH1 gene, may play a role in IBS pathophysiology. While this study was limited by its small sample size, our IBS cohort displayed a trend toward diminished serum vitamin D levels relative to our non-IBS control group.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Interestingly, the IBS-C patients in this population were the most responsive to vitamin D supplementation in terms of a striking improvement across nearly all IBS symptoms. 47 Because IBS-C patients are thought to possess lower gut serotonin levels, 48 the responsiveness of these patients to vitamin D supplementation is consistent with the actions of vitamin D to raise gut TPH1/serotonin levels 25 and with our current hypothesis that vitamin D, via induction of the intestinal TPH1 gene, may play a role in IBS pathophysiology. While this study was limited by its small sample size, our IBS cohort displayed a trend toward diminished serum vitamin D levels relative to our non-IBS control group.…”
Section: Discussionsupporting
confidence: 52%
“…This analysis revealed that 10 of the 11 IBS patients tested exhibited decreased levels of TPH1 relative to a non-IBS sample population, although another study 37 found a statistically insignificant trend towards elevated TPH1 expression in IBS patients. The active hormonal metabolite of vitamin D has been shown to modulate serotonin production within neural 25 and colonic tissue (data not shown). In fact, vitamin D has been proposed as a potential treatment for IBS.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Using these co-abundance groups, these authors measured outcomes in regression models, with prenatal/birth and demographic characteristics as independent predictors, finding that race, mode of delivery, breastfeeding and cord blood vitamin D levels are significantly associated with the composition of the infant gut microbiome (45). Although such a single study does considerably simplify the associations of prenatal factors and breastfeeding with the infant's gut microbiome, it is important to note that variations in vitamin D may also modulate levels of serotonin availability for the melatonergic pathways, with vitamin D increasing levels of tryptophan hydroxylase and, therefore, serotonin synthesis (46). Other work supports a role for breastfeeding in the regulation of the gut microbiome, including in interaction with other factors, such as tobacco use and exposure to pets in pregnancy (47).…”
Section: Breastfeeding: Modulation Of the Gut And Gut-brain Axismentioning
confidence: 99%